Solving the mystery of Obake rice in Africa: population structure analyses of Oryza longistaminata reveal three genetic groups and evidence of both recent and ancient introgression with O. sativa - Labroo, Marlee R.; Clark, Lindsay V.; Zhang, Shilai; Hu, Fengyi; Tao, Dayun; Hamilton, Ruaraidh Sackville; Sacks, Erik J. (Frontiers in Plant Science, 2023)
The undomesticated rice relative Oryza longistaminata is a valuable genetic resource for improvement of the domesticated Asian rice, O. sativa. To facilitate the conservation, management and use of O. longistaminata germplasm, we sought to quantify the population structure and diversity of this species across its geographic range, which includes most of sub-Saharan Africa, and to determine phylogenetic relationships to other AA-genome species of rice present in Africa, including the prevalence of interspecific hybridization between O. longistaminata and O. sativa. Though past plant breeding efforts to introgress genes from O. longistaminata have improved biotic stress resistance, ratooning ability and yield in O. sativa, progress has been limited by substantial breeding barriers. Yet despite the strong breeding barriers observed by plants breeders who have attempted this interspecific cross, there have been multiple reports of spontaneous hybrids of O. sativa and O. longistaminata (aka "Obake") obtained from natural populations in Africa. However, the frequency and extent of such natural introgressions and their effect on the evolution of O. longistaminata had not been previously investigated. We studied 190 O. longistaminata accessions, primarily from the International Rice Research Institute genebank collection, along with 309 O. sativa, 25 O. barthii, and 83 O. glaberrima control outgroups, and 17 control interspecific O. sativa/O. longistaminata hybrids. The materials were analyzed using 178,651 single nucleotide polymorphisms (SNPs) and seven plastid microsatellite markers. This study identified three genetic subpopulations of O. longistaminata, which correspond geographically to Northwestern Africa, Pan-Africa, and Southern Africa. We confirmed that O. longistaminata is, perhaps counterintuitively, more closely related to the Asian species, O. sativa, than African species O. barthii and O. glaberrima. We identified 19 recent spontaneous interspecific hybrid individuals between O. sativa and O. longistaminata in the germplasm sampled. Notably, recent introgression between O. sativa and O. longistaminata has been bidirectional. Moreover, low levels of O. sativa alleles admixed in many predominantly O. longistaminata accessions suggest introgression also occurred in the distant past, but only in Southern Africa.